ANALISIS EFEKTIVITAS JALUR SUKU BUNGA DALAM MEKANISME TRANSMISI KEBIJAKAN MONETER DI INDONESIA (PERIODE 2009-2018) - Rastri Paramita (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2019)
This research was conducted to determine the effectiveness of the interest rate channel in the mechanism of monetary policy in Indonesia. The variables used are policy rates (rSBK) as monetary policy tool, deposit rates (rDeposito), and credit rates (rKredit) as transmission to the real sector and CPI as a proxy of inflation which is the target of monetary policy. The VECM method is used since the variables are cointegrated but are stationary in the first difference. The results impulse response operational targets respond weakly to changes in monetary policy variables because they require a deadline of 5 periods to be able to influence the CPI. While the result of variance decomposition showed the low strength of the rDeposito variable which only reached 1.84 percent, rCredit was only 0,54 in response to the shock of the rSBL. Thus, the effect on CPI is only 1,03 percent. It can be concluded based on this research, the effectiveness of monetary policy which only relies on the policy interest rate channel is less effective in the transmission mechanism of monetary policy in Indonesia for the periode 2009-2018 to impact the inflation.